2014
DOI: 10.1101/009027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral individuality reveals genetic control of phenotypic variability

Abstract: Variability is ubiquitous in nature and a fundamental feature of complex systems. Few studies, however, have investigated variance itself as a trait under genetic control. By focusing primarily on trait means and ignoring the effect of alternative alleles on trait variability, we may be missing an important axis of genetic variation contributing to phenotypic differences among individuals 1,2 . To study genetic effects on individual-to-individual phenotypic variability (or intragenotypic variability), we used … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…1; CS vs. w 1118 ). The extent of this variation was further confirmed in a companion study of wild-derived inbred lines (22). Another potential source of persistent locomotor handedness is morphological asymmetry.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…1; CS vs. w 1118 ). The extent of this variation was further confirmed in a companion study of wild-derived inbred lines (22). Another potential source of persistent locomotor handedness is morphological asymmetry.…”
Section: Resultsmentioning
confidence: 68%
“…cbd KS96 is a missense mutant of Ten-a (25), which encodes a transmembrane protein involved in axon targeting and synapse formation (26,27), and causes severe and widespread defects in the fan-shaped body (FB), ellipsoid body (EB), and noduli (No), leading to high individual-to-individual variation in the gross morphology of the CC (19). Furthermore, a genome-wide association study in a panel of inbred lines implicated SNPs within Ten-a as affecting variability in locomotor handedness (22). This association links natural genetic variation in Ten-a, variability in the function of central complex circuits, and variability in turn bias at the population level.…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about the genetic mechanisms contributing to variance-heterogeneity between genotypes in natural populations. Recently, Ayroles et al [24] showed in an unpublished study that allelic plasticity at an individual locus could be a cause, but beyond that other explanations are still hypothetical. Here, we find that the variance-heterogeneity in leaf molybdenum concentration revealed in a collection of wild-collected A.…”
Section: Discussionmentioning
confidence: 99%
“…epistasis or gene-by-environment interactions) [16,21,25]. The first suggestive empirical evidence for variance-heterogeneity being a property of a single locus was recently presented in an unpublished study by Ayroles et al [24]. In that study, a vGWA association to a behavioral phenotype in the Dropsophila Genome Reference Panel (DGRP) was determined to be driven by a mutation in the Ten-a gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation